Pengaruh Kuat Arus dan Waktu Pengelasan pada Proses Las Titik (Spot Welding) Terhadap Kekuatan Tarik dan Mikrostuktur Hasil Las dari Baja Fasa Ganda (Feritte-Martensite) - Agustriyana, Lisa; Suryawan, Yudi; Sugiarto, Sugiarto (Jurnal Rekayasa Mesin, 2011)
This research was conducted to investigate the appropiate spot welding variable to get the maximum tensile strength. The highest of tensile strength referred as good quality of weldment.The plate was made from low carbon steel with phase ferrite and martensite. The current of welding used 0.9 kA, 1.6 kA, dan 1.85 kA with welding time were 0.25, 0.5 , 0.75 and 1 second. Mechanical properties testing done involved tensile strength to know shear strength of weld joint. Microstructure test used optical microscope.The results show that spot welding with thecurrent of 1.85kA and welding time of 1 second has the highest tensile strength (about 237.04N/mm2). On the other hand, the lowest tensile strength (150 N/mm2) was produced by combination of 0.9 kA and 0.25 second welding time. It was caused by recrystallization phasedeformation on steel.Keywords: current, welding time, tensile strength, spot weld